Genomically personalized therapy in head and neck cancer. Issue 1 (December 2016) - Aung, Kyaw; Siu, Lillian
Abstract The current treatment paradigm in head and neck cancer does not adequately address its clinical and biological heterogeneity. Data from genomic profiling studies in head and neck squamous cell carcinoma (HNSCC) have revealed the molecular features that are unique to HNSCC subgroups. This progress in the understanding of HNSCC biology provides an opportunity to develop personalized therapies for patients with distinct molecular subtypes to achieve better clinical outcomes including survival. However there are several well-recognized challenges that need to be overcome before genotype-matched therapies make precision medicine a reality for patients with HNSCC. Selection of appropriate patients for biomarker directed clinical trials based on sound scientific rationale will be critical in making cancer genomics more applicable in this malignancy.